Axial behavior of basalt FRP-confined reinforced concrete columns with square sections of different corner radii. (1st January 2023) - Xie, Dong; Hu, Zhongjun; Wang, Boxin; Zhao, Kang; Shi, Yatao
Highlights: Parameters that influence the axial compressive properties of BFRP-confined square RC columns were analyzed. The specific impacts of corner radius on the development of hoop strains in the BFRP wraps were analyzed. A prediction equation of strain efficiency factor for BFRP-confined square RC columns was proposed. Abstract: Axial compressive tests were conducted on fourteen BFRP-confined square reinforced concrete (RC) columns, involving variations of the corner radius and FRP layers. The test results demonstrate that the Basalt-FRP confinement leads to strength improvement, such as 109% gain at a corner radius ratio of 0.6, and also improves the ductility of the RC column. The stress–strain response has a bilinear type, and the difference in confinement level is mainly reflected in the inelastic range. Furthermore, the observation of the distribution of hoop strain values shows that the confinement pressure uniformity increases with the corner radius. Finally, a prediction equation for the strain efficiency factor is proposed to improve the accuracy of existing square section strength models. A modified strength model of Wu and Zhou shows good agreement with the experimental results.